Information Systems Auditing: Roles, Methods, and Challenges in Ensuring the Reliability of Organizational Information Systems - Ade Triawan; Yulia Yulia; April Zahmi (The Future of Education Journal, 2026)
The rapid advancement of information technology has increased the need for organizations to implement information systems that are reliable, secure, and effective. Information Systems Audit (IS Audit) has become an essential mechanism for evaluating whether an organization's information systems align with business objectives, organizational policies, and applicable standards. This article aims to examine the concepts, objectives, types, procedures, and challenges associated with Information Systems Auditing. Using a literature review approach, the study analyzes books, scholarly journals, and audit-related documents. The findings indicate that Information Systems Auditing extends beyond technical evaluation to encompass management, regulatory compliance, and risk management aspects. Effective audit practices provide valuable insights that support strategic decision-making and strengthen organizational IT governance.